National Ocean Survey Bathymetric Mapping Program - Banks, Norman E. (The International Hydrographic Review, 2015)
This is a summary of a lecture given at the XIIth I.H. Conference by Captain Lavon L. Posey, NOS, NOAA, on behalf of the author. Captain Posey worked closely with Mr. Banks in developing a clear description of the Bathymetric Programme to obtain the necessary funds to make it an ongoing and permanent programme in NOS.